2D-imaging of absolute OH and H2O2 profiles in a He–H2O nanosecond pulsed dielectric barrier discharge by photo-fragmentation laser-induced fluorescence. (1st January 2023) - van den Bekerom, Dirk; Tahiyat, Malik M; Huang, Erxiong; Frank, Jonathan H; Farouk, Tanvir I
Abstract: Pulsed dielectric barrier discharges (DBD) in He–H2 O and He–H2 O–O2 mixtures are studied in near atmospheric conditions using temporally and spatially resolved quantitative 2D imaging of the hydroxyl radical (OH) and hydrogen peroxide (H2 O2 ). The primary goal was to detect and quantify the production of these strongly oxidative species in water-laden helium discharges in a DBD jet configuration, which is of interest for biomedical applications such as disinfection of surfaces and treatment of biological samples. Hydroxyl profiles are obtained by laser-induced fluorescence (LIF) measurements using 282 nm laser excitation. Hydrogen peroxide profiles are measured by photo-fragmentation LIF (PF-LIF), which involves photo-dissociating H2 O2 into OH with a 212.8 nm laser sheet and detecting the OH fragments by LIF. The H2 O2 profiles are calibrated by measuring PF-LIF profiles in a reference mixture of He seeded with a known amount of H2 O2 . OH profiles are calibrated by measuring OH-radical decay times and comparing these with predictions from a chemical kinetics model. Two different burst discharge modes with five and ten pulses per burst are studied, both with a burst repetition rate of 50 Hz. In both cases, dynamics of OH and H2 O2 distributions in the afterglow of the discharge are investigated. Gas temperatures determined from the OH-LIF spectra indicate that gas heating due to the plasma is insignificant. The addition of 5% O2 in the He admixture decreases the OH densities and increases the H2 O2 densities. The increased coupled energy in the ten-pulse discharge increases OH and H2 O2 mole fractions, except for the H2 O2 in the He–H2 O–O2 mixture which is relatively insensitive to the additional pulses.